Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1037/neu0000115
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmic priming enhances speech production abilities: Evidence from prelingually deaf children.

Abstract: These results suggest that musical rhythmic priming can enhance phonological production in HI children via an enhanced perception of the target sentence. Overall, these findings suggest that musical rhythm engages domain-general expectations which can enhance both in perception and production of speech.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 36 publications
6
40
0
1
Order By: Relevance
“…Rhythmic training sessions have proved useful to enhance the phonological perception of words and sentences [1,2,3], to help primary school children acquire reading skills [8], to improve oral production by children with cochlear implants [4], and to improve stress placement [5] and general pronunciation in learners of English [6,7]. In this study, we extend previous findings by showing in Exp.…”
Section: General Discussion and Conclusionsupporting
confidence: 80%
See 2 more Smart Citations
“…Rhythmic training sessions have proved useful to enhance the phonological perception of words and sentences [1,2,3], to help primary school children acquire reading skills [8], to improve oral production by children with cochlear implants [4], and to improve stress placement [5] and general pronunciation in learners of English [6,7]. In this study, we extend previous findings by showing in Exp.…”
Section: General Discussion and Conclusionsupporting
confidence: 80%
“…Priming studies by Cason and collaborators have shown that the phonological processing of speech by adult participants is enhanced by the temporal expectations generated by a musical rhythmic prime [1,2]. Regarding production skills, Cason et al [4] showed that the same priming effect benefits hearing-impaired children with cochlear implants. Similarly, Bhide et al [8] found that a twomonth program of phonological and rhythmic training helped children who were considered poor readers to improve their literacy skills.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cason and Schön (2012; [19]) previously reported a crossdomain priming effect of music on speech processing, which was reflected by a similar increased negativity when the metrical structure of the spoken target word did not match the rhythmic structure of the musical prime. Several other findings have since shown that temporal expectancies generated by rhythmically regular musical primes can facilitate spoken language processing in typical adults (e.g., [20,47]), and children [48,49], as well as adults with Parkinson's disease [50], children with cochlear implants [51], and children with language disorders [52]. This beneficial effect may stem from the regular rhythmic structure of the musical prime, which provides temporally predictable cues to which internal neural oscillators can anchor [20].…”
Section: Discussionmentioning
confidence: 98%
“…Once the metrical rules, which provide important cues for speech segmentation within the continuous speech stream, have been acquired, speech meter contributes to phonological (Pitt & Samuel, 1990), semantic (Schwartze et al, 2011) and syntactic (Roncaglia-Denissen et al, 2013) processing. Musical rhythmic priming, using meter, has been revealed to enhance phonological production in hearing impaired children, due to an enhanced perception of sentences (Cason et al, 2015). Furthermore, in the context of speech rehabilitation therapies, musical rhythm has been revealed to be a fluency-enhancing tool (Thaut, 2013).…”
Section: Introductionmentioning
confidence: 99%